Answer:678
Step-by-step explanation:im dumb
Answer:
its 6x
Step-by-step explanation:
The answer is -6
(9-15)=-6
(-8+2)=-6
(24-30)=-6
-(-6)+(-6)-(-6)= -6
9514 1404 393
Answer:
C
Step-by-step explanation:
The step shown indicates that y was eliminated from the equations. For choices A, B, D, this is done by adding the equations together (the y-coefficients are opposites). The result of doing that gives x-terms of 4x, 0x, and 0x, respectively. These x-terms do not match the one given: 2x.
For choice C, the y-term is eliminated by subtracting twice the second equation from the first. Doing that gives ...
(4x +2y) -2(x +y) = (14) -2(3)
4x +2y -2x -2y = 14 -6 . . . . eliminate parentheses
2x = 8 . . . . . . . . . . . . . . collect terms